Studies On The Entomogenous Fungus Associated With Cowpea Aphid - Faizal MH (Department of Agricultural Entomology, College of Agriculture, 1992)
Studies were conducted on the entomogenous fungus Fusarium pallidoroseum (Cooks) Sacc. infecting cowpea aphid Aphis craccivora Koch. The infected aphids turned pale and assumed brownish black discolouration. Death occurred in 24 to 72 hours after infection and mycelial growth appeared on the cadavers 24 to 48 hours after death. For mass production of the fungus, wheat bran and rice bran appeared to be comparatively suitable as they recorded maximum growth, sporulation and virulence of the pathogen. Maximum sporulation was noticed 8 days after inoculation. Culture substrates subjected to full heat sterilization produced maximum growth and sporulation of the fungus followed by those subjected to full solarization. A mortality per cent of 99.57 was observed when aphids were sprayed with culture filtrate of F. pallidoroseum grown in Richard’s medium indicating the presence of toxins. Studies on the effect of pesticides on the growth of the fungus showed that mercaptothion and monocrotophos were the least inhibitory. Fenthion showed the least inhibition of sporulation. HCH, captan and zineb completely inhibited the growth. Sporulation was completely inhibited in all the fungicidal treatments. Under laboratory conditions spore suspension of the fungus in water was found to be superior to the spore formulations tried. Among the formulations wettable powder with diatomaceous earth as inert material was found to cause more mortality followed by wettable powder with talc as inert material. Dust using talc as inert material was found to be the least effective. Spore suspension in water, wettable powder formulation of fungal spores with diatomaceoue earth as inert material and quinalphos 0.05 per cent were found to be equally effective in bringing down the population of aphids under field conditions. The virulence of spores of F. pallidoroseum in formulation was found to decrease with increase in storage period and it retained substantial virulence up to four days of storage.